Analisis Ketahanan Rangka Stasiun Pengisian Kendaraan Listrik Berbasis Panel Surya Portabel Terhadap Laju Angin - Muhammad Imam; Ade Sunardi; Mohamad Zaenudin (Integrated Mechanical Engineering Journal, 2023)
High wind velocity can induce external pressures and loads on the structural framework of an Electric Vehicle Charging Station (EVCS), jeopardizing the overall stability and structural integrity of the framework. The objective of this research is to ascertain the magnitude of aerodynamic drag force and the maximum pressure values on the surface of the EVCS framework, with respect to variations in wind velocity. The methodology employed in this study involves Computational Fluid Dynamics (CFD) simulations utilizing the Solidworks Flow Simulation. Three wind velocity scenarios were considered: 3 km/h, 6 km/h, and 9 km/h, allowing for the observation of airflow acceleration phenomena, aerodynamic drag force values, and peak pressure distributions on the EVCS framework's surface. Research findings reveal that the aerodynamic drag force at a wind velocity of 3 km/h measures 22,34 N, escalating to 90,42 N at 6 km/h wind velocity, and reaching 202,7 N at 9 km/h wind velocity. Furthermore, the highest-pressure value at a wind velocity of 3 km/h is 101325,45 Pa. As the wind velocity increases to 6 km/h, the maximum pressure value rises to 101338,18 Pa. Under the condition of the highest input wind velocity, i.e., 9 km/h, the peak pressure reaches 101353,46 Pa.